Kontruksi Nilai-Nilai Nasionalisme Pada Film (Analisis Isi "Film Soekarno" Untuk Media Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan) - Umam, Lutfi Khoirul (2016)
Education, Muhammadiyah University of Surakarta. Januari, 2016. The movie which very easily accessible by anyone must educate and provide learning for anyone watching. Among the wide range of films that exist in society and also contains the values of nationalism authors chose the film Soekarno for the research because the movie contains many educational values include the values of nationalism which is now beginning to fade among teenagers. Value nationalism is said to be successful if the learning Pancasila and Citizenship Education fulfilling the given indicators. This study indicators were used as a benchmark among others: able to sacrifice for the nation, to love the homeland, proud nation Indonesia, uphold the unity of the nation and the state, promoting the association for national unity. Research on the values of nationalism is not only done at this time, but it has been done among others by Mariana (2011), shows that the Nagabonar Jadi 2 movie gives a message about the behavior and mindset of the people who began promoting the values of nationalism and patriotism, and considers that value is irrelevant used in this present life. Nagabonar in the movie is portrayed as having a spirit of nationalism and patriotism, attitudes that still fought in the midst of modern society in the era of globalization. Umar figures showed him-right in the audience even with the limitation of income and insight, but clever in dealing with life and be ever grateful in life. Nagabonar Jadi 2 also illustrates a tolerant attitude shown temannyayang Bonaga and friends of different religions, ethnicities, and cultures but still respect each other and respect. They are a tangible manifestation of the diversity of ethnicity, race, customs, culture, language and religion in Indonesia. Through tolerance can be realized life in harmony and peace. Nagabonar Jadi 2 Movie can be used as an alternative medium of learning Pancasila and Citizenship Education, because it contains the value of nationalism and patriotism in the era of globalization that is packaged in an atmosphere of modern life. In accordance with the reality of people's lives today so that viewers easily grasp and interpret the messages contained in the film.